Strategic Negotiations in the Process of the EU Enlargement: A Game-Theoretical Application to the Agricultural Dossier - Valentin Cojanu (Romanian Journal of European Affairs)
This material attempts to predict the results of negotiations in the process of the EU enlargement. The analysis is to shed light on the underlying determinants of possible outcomes and to suggest with anticipation improved ways of conduct. The interaction between nation-states is modeled in classes of games or strategic structures of interaction on the basis that the incentives of each party are revealed by their behavioral stance. The findings present a detailed analysis of bargaining power and offer predicted solutions to negotiations for the cases of the two candidate countries – Poland and Romania – considered in the application. The model’s predictions closely follow the results of negotiations in every significant detail.